2009
DOI: 10.1051/ocl.2009.0268
|View full text |Cite
|
Sign up to set email alerts
|

Future prospects for palm oil refining and modifications

Abstract: Palm oil is rich in minor components that impart unique nutritional properties and need to be preserved. In this context, refining technologies have been improved, with the dual temperature deodorizer, the double condensing unit and the ice condensing system. The DOBI is a good tool to assess quality of the crude palm oil and its ability to be properly refined. Specially refined oils open a market for new high quality products (golden palm oil, red palm oil, white soaps, etc.). Palm oil is a good candidate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 4 publications
0
10
0
15
Order By: Relevance
“…The latter distorted round shape is ascribed to a fat crystal network, which dictates the shape of the W/O/W sPMF globules. sPMF consists mainly of nonsurface active triacylglycerols, which suggests predominantly bulk crystallization in the oil volume of the W/O/W globules. Cryo‐SEM images of the W/O/W sPMF (Figure a,b) validate the small fat globule size measured by light scattering and reveal the existence of a crystalline fat matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The latter distorted round shape is ascribed to a fat crystal network, which dictates the shape of the W/O/W sPMF globules. sPMF consists mainly of nonsurface active triacylglycerols, which suggests predominantly bulk crystallization in the oil volume of the W/O/W globules. Cryo‐SEM images of the W/O/W sPMF (Figure a,b) validate the small fat globule size measured by light scattering and reveal the existence of a crystalline fat matrix.…”
Section: Resultsmentioning
confidence: 99%
“…From the data obtained, for all three varieties, the DOBI meets the requirement for excellent CPO at day 0, when it is harvested (control). However, after 7 days' storage (except in tenera), a DOBI below 2 testifies an oil with very poor quality, which is more difficult to refine [2]. It has been reported that after short-term storage of the palm fruits (30 min to 120 min), the chopped fruits produced a lower quality of palm oil [7].…”
Section: Carotene Content and Dobimentioning
confidence: 99%
“…The feed CPO has been shown to contain carotene at 632 ppm [11]. The carotene criterion determined by the specification and quality requirements for Lotox CPO was 600-700 ppm [2]. From the data obtained, the carotene content of dura ranged from 343-568 ppm, which was the value at day 0 (568.42 ppm) and is thus only suitable as a standard; after 7 to 28 days' storage, the carotene content decreased to < 500 ppm.…”
Section: Effect Of Storage Time On Palm Oil Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is one of processing industries in the downstream sector that connect with overall entities which it is the oil palm refinery. This industry produces many type derivative products of oil palm nevertheless they are processed through the different technology of processing industry [5].…”
Section: Introductionmentioning
confidence: 99%